Using audio in secure device pairing. (24th February 2009) - Goodrich, Michael T.; Sirivianos, Michael; Solis, John; Soriente, Claudio; Tsudik, Gene; Uzun, Ersin
Secure pairing of electronic devices is an important issue that must be addressed in many contexts. In the absence of prior security context, the need to involve the user in the pairing process is a prominent challenge. In this paper, we investigate the use of the audio channel for human-assisted device pairing. First we assume a common (insecure) wireless channel between devices. We then obviate the assumption of a pre-existing common channel with a single-channel device pairing approach only based on audio. Both approaches are applicable to a wide range of devices and place light burden on the user.